USAGE OF METAPHORIC MEANS IN ADVERTISING TEXTS: On the Basis of English, Azerbaijani and Russian Materials - Vusala Mammadova (International Journal of Innovative Technologies in Social Science, 2023)
In advertising text, metaphor often takes a dominant position: it affects the will and feelings of consumers, prompting them to act. With its help, only the necessary and positive properties and characteristics of the product or service, their merits, are updated, which makes it difficult for consumers to evaluate them objectively. Main points of view of Aristotle, and those of some modern linguists (Sklyarevskaya G.N., Richards A.A, Black M., Zaretskaya, Y.N., Kharchenko, V. K., etc.) of metaphors are investigated in this research. In this article, metaphorical models used in advertising are studied. Specialists identify fifteen functions of metaphor in advertising: nominative, informative, mnemonic, style-creating, text-creating, genre-creating, heuristic, explanatory, emotional-evaluative, ethical, automatic suggestion, coding, conspiratorial, playful, ritual. Together with the above-given features, metaphors are considerer to be “a fast and powerful means to convey an idea.”, and in advertisings they lead to- brightness of advertising image; the advertisement is easily understood by the recipient; identification through stereotypes; the speed of communication (short texts give faster and more information). So, metaphor is defined as a hidden comparison, carried out by applying the name of one object to another, and thus revealing some important feature of the other.